The narrative of a transformative leader - Urbina Montana, Maria L. (Družboslovne razprave, 2025)
The paper explores how General Augusto Pinochet’s death in 2006 catalysed a shift in the collective memory of Chile, reframing him as a transformative leader who modernised the nation with neoliberal reforms. Rather than pursuing systematic empirical analysis, the paper adopts a conceptual approach that draws on Basil Bernstein’s theory of recontextualisation and Mark Fisher’s concept of capitalist realism to examine the contribution made by media narratives to this reframing. Through thematic analysis of cross-platform cultural texts, including news coverage and the films The Death of Pinochet and El Conde, it is argued that these narratives strategically separate economic success from political repression, marginalising working-class memory and reinforcing neoliberal hegemony. The Chilean case is situated within broader global memory politics, with a comparative reference made to Margaret Thatcher’s legacy in the United Kingdom. By highlighting the ideological work performed by historical narratives, the paper contributes to debates on memory, neoliberalism, and the erasure of resistance in post-authoritarian societies.
Keywords: Augusto Pinochet; Autusto Pinochet; capitalist realistm; cross platform discourse; Državni udar (Čile, 1973); kapitalistični realizem; medplatformski diskurz; memory; spomin; transformative leader; transformativni voditelj